Digital health literacy and subjective wellbeing in the context of COVID-19: A cross-sectional study among university students in Ecuador - Rivadeneira, María F.; Salvador, Carmen; Araujo, Lorena; Caicedo-Gallardo, José D.; Cóndor, José; Torres-Castillo, Ana Lucía; Miranda-Velasco, María J.; Dadaczynski, Kevin; Okan, Orkan (Frontiers in Public Health, 2023)
Background: The COVID-19 pandemic has generated an avalanche of information, which, if not properly addressed, generates uncertainty and limits healthy decision-making. On the other hand, the pandemic has exacerbated mental health problems among young people and adolescents, causing a worsening of their well-being. Previous studies have found that digital health literacy has a positive impact on people's attitudes towards the disease. This study aimed to analyze the association between digital health literacy on COVID-19 with subjective well-being in university students. Methods: A cross-sectional study was developed in 917 students from Ecuador. Subjective well-being was measured with the World Health Organization Well-Being Scale. Digital health literacy was assessed using the Spanish-translated version of the Digital Health Literacy Instrument adapted to the context of the COVID-19 pandemic. Bivariate and multivariate linear regressions were performed. Results: Digital health literacy and subjective wellbeing proofed to be significantly higher among males and among students with higher social status. The association between digital health literacy and subjective wellbeing was significant; for each increase of one point in the digital health literacy scale, an average increase of 0.5 points could be observed on the subjective wellbeing scale (IC 95% 0.3 – 0.6, p-value <0.001). This correlation persisted after adjust by demographic and socioeconomic variables. Conclusion: Improving digital literacy in health would improve the subjective well-being of university students. It is suggested strengthen the digital health literacy through public and university policies that promote access, search skills and discernment of digital information. Socioeconomic and gender inequalities related to digital health literacy need to be further investigated.